(untitled) (Educação e Pesquisa, 2009)
Articulating dance and education, this article speaks of possibilities. Considering the educative-formative processes of educators as a driving focus, it presents and discusses issues enriched in the context of a doctorate research conducted with different groups of educators, and developed through the use of " gatherings to dance in circles" . In the relationship constructed between the experience with a specific form of dance - the circular dance - and the reflection upon teacher education some thematic units were identified. Among them stands the need to contemplate in the journey of formation the aesthetic dimension by cultivation of the " sensitive being" present-hidden in the adult-educator. We therefore consider the implication of proposals that contribute to the construction of educative processes that are more whole, bringing together again reason and emotion, cognition and affection. In developing this research, studying the symbology of the circle turned out to be essential, and in the present article it constitutes the central point of the discussion. The perfection and the absence of distinction or division are symbolic properties of the circle. Its image evokes equilibrium, totality, integration of differences, interdependence. Wheel, circle, mandala: are these not beautiful images for the educative practice? The dancing circle: would it not be an opportunity for the learning of circularity in education? Running along these issues that involve the potentiality of the symbol, the text proposes a discussion about the necessary circularity of educative processes.